Role of fatty acids in pathogenetic mechanisms of NAFLD progression among type 2 diabetes patients - Mykhalchyshyn, G. (Journal of Education, Health and Sport, 2020)
The goal of our case-control research was to study the associations between speed progression of NAFLD and the level of fatty acids among patients with the type 2 diabetes. All patients were divided into two groups: with speed (n=38) and slow (n=44) progression of fibrosis. We studied the level of saturated, monounsaturated and polyunsaturated fatty acids and their rate. Our study showed higher median value of sum of saturated fatty acids level in the group of patients with speed progression of fibrosis (51,6% and 45,75%, p=0,001) and lower median value of arachidonic acids than in the group of patients with slow progression of fibrosis (10,5 and11,5 inthe group of slow fibrosis progression, р=0,049). In the group of patients with speed fibrosis progression saturated fatty acids prevailed unsaturated fatty acids (Ме=1,02). According to our data, the risk factor of speed progression of fibrosis among patients with type 2 diabetes and NAFLD, is the rate of saturated and unsaturated fatty acids. We found the significant associations between the rate of saturated and unsaturated fatty acids and the speed progression of fibrosis (OR 77,3; р=0,004). Abbreviations: BMI, body mass index, IR, insulin resistance, NAFLD, nonalcoholic fatty liver disease, OR, odds ratio, FFA, free fatty acids, FA, fatty acids, LDL, low density lipoproteins, RPF, median rate of fibrosis progression, TG, triglycerides